Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1745-9125.2010.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Moral Norms and Instrumental Incentives in Crime Causation*

Abstract: Rational choice theories (RCTs) of crime assume actors behave in an instrumental, outcome‐oriented way. Accordingly, individuals should weight the costs and benefits of criminal acts with subjective probabilities that these outcomes will occur. Previous studies either do not directly test this central hypothesis or else yield inconsistent results. We show that a meaningful test can be conducted only if a broader view is adopted that takes into account the interplay of moral norms and instrumental incentives. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 73 publications
6
101
0
2
Order By: Relevance
“…After all, it is usually infeasible and undesired to monitor people's behavior for a 100 %. However, people who feel bounded by moral norms are not influenced by such instrumental reasons (Kroneberg et al 2010;Wenzel 2004). So, if a sanction evokes moral reasons to show the desired behavior, people are likely to adhere to the rules even when the chances that they will be caught if they do not, are small (Mulder and Nelissen 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After all, it is usually infeasible and undesired to monitor people's behavior for a 100 %. However, people who feel bounded by moral norms are not influenced by such instrumental reasons (Kroneberg et al 2010;Wenzel 2004). So, if a sanction evokes moral reasons to show the desired behavior, people are likely to adhere to the rules even when the chances that they will be caught if they do not, are small (Mulder and Nelissen 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In criminology it has been advocated that the interplay of moral norms and instrumental incentives should be taken into account. Kroneberg et al (2010) concluded that shoplifting and tax fraud was only based on instrumental rationality for people who did not feel bounded by moral norms. For those with strongly internalized norms, instrumental incentives had no influence.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of crime opportunity also refers to the fourth principle of microeconomics (Mankiw 1997) -people respond to incentives -and there the degree of necessary opportunity or incentive depends on the individual. The incentives could range from vindication to morality, ethics, altruism, or determinism (Ekwall 2009a;Kroneberg et al 2010). Altogether, this leads to that the relationship between threats (motivated perpetrator) and countermeasures (security) linked around a desirable outcome or object, are complex and contextual depended.…”
Section: Lack Of Capable Guardianmentioning
confidence: 99%
“…The more interesting examples of these opportunities will be explained and described later in this thesis. The most important thing to remember about crime opportunity is that an opportunity alone does not explain why a crime occurs because a crime needs a motivated perpetrator and opportunity to occur [64]. The theory of crime opportunity also refers to the fourth principle of microeconomics [57] -people respond to incentives -and there the degree of necessary opportunity or incentive depends on the individual.…”
Section: Opportunity To Crimementioning
confidence: 99%
“…The theory of crime opportunity also refers to the fourth principle of microeconomics [57] -people respond to incentives -and there the degree of necessary opportunity or incentive depends on the individual. The incentives could range from vindication to morality, ethics, altruism, or determinism [3,64]. Altogether, this leads to that the relationship between threats (motivated perpetrator) and countermeasures (security) linked around a desirable outcome or object, are complex and contextual depended.…”
Section: Opportunity To Crimementioning
confidence: 99%